Еnergy cooperation between the EU and Сentral Asia (Халықаралық қатынастар және халықаралық құқық сериясы, 2017)
The article analyzes the relationship between the European Union and the Republic of Kazakhstan in the framework of the energy sector. Kazakhstan is a country with vast energy resources, therefore it is one of the most important players in this industry. The European Union, in turn, is a major consumer of energy in the eastern hemisphere. The energy dialogue is a key component of Kazakhstan’s cooperation with the EU. Relationships are being built in the framework of the Energy Charter Treaty and the support of programs such as TRACECA and INOGATE.